Improvised intracranial pressure monitors in the developing World: A scoping review - Damilola Jesuyajolu; Abdulahi Zubair; Temidayo Osunronbi; Gamaliel Aremu (Interdisciplinary Neurosurgery, 2024)
Introduction: Due to less than favorable conditions in low and low-middle-income countries, surgeons have had to carefully craft improvised devices to try and mimic the functionality and level of innovation in the developed countries. In this review, we sought to examine the existing literature to review the alternative ways by which intracranial pressure is measured when standard devices are inaccessible. Furthermore, we aimed to see how these devices are made and how much they cost. Methodology: The PRISMA extension for scoping reviews was utilized. Databases and Grey Literature (PubMed, Google Scholar, and AJOL) were searched extensively, and papers reporting on the use of improvised intracranial pressure monitoring were included. The devices were grouped into two setups and described extensively. The cost of the devices was also estimated. We extracted the relevant information after identifying the papers that would be used in our review study. Results: 3 papers satisfied our eligibility criteria and were used in the review. Two setups were discussed. The first setup involved the use of a makeshift device made up of a size 6 feeding tube/soft silicon catheter, a central venous pressure manometer and sterile 0.9% saline as the coupling agent, while the second setup involved the use of a size 8 feeding tube, a pressure line extension, dome, transducer, and monitor. Both devices cost less than USD 20, a price far cheaper than the standard ICP devices quoted at about USD 800. Conclusion: Our review posits that these makeshift devices have certain advantages and may be useful in the rural and less developed parts of the world. It also serves as an area for intervention, especially in the context of global neurosurgery.